The Influence of Life Satisfaction, Self-determination and Sports Practices on Intellectual Ability of Football Players: Mediating Role of Coaching Style - Wei Zheng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
A player's intellectual ability could enhance their performance in the field, and in doing so, lead the team towards success. This study aims to examine the factors (life satisfaction, self-determination and sports practices) that impact the intellectual ability of football players in China. Moreover, the study examines the mediating impact of coaching style vis-a-vis life satisfaction, self-determination, sports practices and intellectual ability of football players in China. This study followed uses quantitative methods of data collection through questionnaires administered to China's football players selected through simple random sampling. For hypothesis testing, smart-PLS has been executed to analyze the data. The results revealed that life satisfaction and sports practices have a positive association with football players' intellectual ability in China. The results also examined that coaching style has positively mediated the nexus among life satisfaction, self-determination, sports practices and intellectual ability of football players in China. These outcomes help the regulators while formulating policies related to the players' intellectual ability.